2015
DOI: 10.1016/j.jneumeth.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate treatment during adolescence on norepinephrine transporter function in orbitofrontal cortex in a rat model of attention deficit hyperactivity disorder

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is associated with hypofunctional medial prefrontal cortex (mPFC) and orbitofrontal cortex (OFC). Methylphenidate (MPH) remediates ADHD, in part, by inhibiting the norepinephrine transporter (NET). MPH also reduces ADHD-like symptoms in Spontaneously Hypertensive Rats (SHRs), a model of ADHD. However, effects of chronic MPH treatment on NET function in mPFC and OFC in SHR have not been reported. In the current study, long-term effects of repeated treatment with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Computational models reproducing experimental results (Gao and Holmes, 2007 ; Patel and Joshi, 2015 ), particularly on the roles of adrenoceptors in behavioral tasks (Chandler et al, 2014b ; Chandler, 2015 ; Somkuwar et al, 2015 ) are starting to reach a remarkable level of sophistication, and will undoubtedly contribute to integrate the large amount of experimental results collected along many decades on the adrenergic effects on the modulation of intrinsic neuronal conductances and long- and short-term plasticity. Possibly the most important related issue concerns the specific mechanism through which distress elicits maladaptive plasticity, turning a number of physiologically connected, functional, brain areas into a series of dysfunctional circuits as seen in psychiatric disease.…”
Section: Discussionmentioning
confidence: 75%
“…Computational models reproducing experimental results (Gao and Holmes, 2007 ; Patel and Joshi, 2015 ), particularly on the roles of adrenoceptors in behavioral tasks (Chandler et al, 2014b ; Chandler, 2015 ; Somkuwar et al, 2015 ) are starting to reach a remarkable level of sophistication, and will undoubtedly contribute to integrate the large amount of experimental results collected along many decades on the adrenergic effects on the modulation of intrinsic neuronal conductances and long- and short-term plasticity. Possibly the most important related issue concerns the specific mechanism through which distress elicits maladaptive plasticity, turning a number of physiologically connected, functional, brain areas into a series of dysfunctional circuits as seen in psychiatric disease.…”
Section: Discussionmentioning
confidence: 75%
“…Both DAT and NET clear extracellular DA in prefrontal cortex (Moron, Brockington et al 2002, Berridge, Devilbiss et al 2006). In adult SHR, NET function in orbitofrontal cortex (OFC; a subregion of the prefrontal cortex) is increased compared to WKY and WIS (Somkuwar, Kantak et al 2015). Also, MPH treatment during adolescence normalized NET function in adult SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous neurochemical studies assessing noradrenergic transmission in prefrontal cortex of SHR and WKY may explain why the effect of idazoxan is found only in SHR that received adolescent atomoxetine. One study showed that the norepinephrine system is under less inhibitory control (less α2 agonist-induced inhibition of potassium-stimulated norepinephrine release) in non-medicated SHR than WKY (Russell et al 2000), an effect that is consistent with the compensatory increase in the rate of norepinephrine uptake or clearance in frontal cortex of non-medicated SHR vs. WKY (Myers et al 1981) or in orbitofrontal cortex of non-medicated SHR vs. WKY and WIS (Somkuwar et al 2015). If norepinephrine clearance is faster in SHR, then the consequent low extracellular noradrenergic tone in cortex of non-medicated SHR compared to the control strains may contribute to the robust strain differences in PR breakpoints, as reduced noradrenergic transmission at post-synaptic sites within prefrontal cortex may enhance cocaine self-administration (see section 4.1 above).…”
Section: Discussionmentioning
confidence: 92%